Nicotine reduces cell viability and induces oxidative stress in human gingival fibroblasts (Universa Medicina, 2024)
BackgroundNicotine, as the main component of cigarettes, is known to interfere with the proliferation of human gingival fibroblasts (HGFs) and can trigger oxidative stress. This study aimed to analyze the impact of nicotine on viability, expression of the antioxidant Nrf2, levels of the product of oxidative stress malondialdehyde (MDA), and the migration capacity of HGFs.MethodsAn experimental laboratory study used fibroblasts isolated from healthy human gingiva. The cells were grouped into the non-treatment control group (NTC), the solvent control (SC), and the treatment groups, exposed to nicotine at various concentrations for twenty-four hours. Cell viability was assesed using the cell counting kit-8 (CCK-8), Nrf2 expression was examined using ELISA, MDA level was measured using an MDA kit, and migration capacity was assessed using a scratch assay. Statistical analysis used one-way Anova or Kruskal-Wallis test. A p-value of